Jurisprudence of Technology Laws - Bhatnagar, Shivi (Integrated Journal for Research in Arts and Humanities, 2024)
In today's rapidly evolving world of science and technology, our interactions with devices like Alexa and Siri have become as commonplace as conversations with family members. Initially, technology served to create products, generate services, or achieve desired results. However, the advent of affordable and accessible new technologies has ensnared everyone in its web, even influencing mundane activities such as drinking water, with smartwatches reminding us to hydrate. Services like Swiggy and Zomato deliver food within minutes, fostering a culture of convenience that can make us lethargic. Technology's impact spans across booking travel tickets, movie reservations, online shopping, and virtual classes, making us increasingly reliant on it. Traditionally, the essentials for human life were "Roti, Kapda, aur Makan" (food, clothing, and shelter), but now smartphones and internet access have joined this list. While technology's success hinges on data availability, it also raises significant concerns about privacy and security. The Supreme Court of India has highlighted the misuse of social media for spreading falsehoods and violating privacy rights. Social media's pervasive influence affects all age groups, particularly children, exposing them to inappropriate content and leading to premature mental maturity. This exposure results in risks like cyberbullying, sextortion, cyber trafficking, child pornography, and online fraud. Consequently, children and parents face mental health issues, academic distractions, and potential criminal involvement. The rise in cybercrime has placed India among the top ten countries affected, with Russia leading the list. The growing dependence on technology necessitates a balanced approach to leverage its benefits while safeguarding against its threats.